2010
DOI: 10.1002/jnr.22427
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of annexin A5 as a biomarker for Alzheimer's disease using neuronal cell culture and mouse model

Abstract: Alzheimer's disease (AD) differs from other forms of dementia in its relation to amyloid beta peptide (Abeta). Abeta, a proteolytic product of amyloid precursor proteins (APP), has a toxic effect on neuronal cells, which involves perturbation of their Ca(2+) homeostasis. This effect implies that changes of protein expression in neuronal cells with calcium stress should provide a molecular marker for this disease. In the present study, we used the supernatant from a neuronal cell culture after incubation with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 41 publications
2
26
2
Order By: Relevance
“…The subjects of this study were 279 control subjects from one of our previous studies [12], 145 patients with probable AD according to the NINCDS/ADRDA criteria [13], and 50 subjects with probable DLB according to the latest consensus diagnostic criteria published in 2005 [11]. To obtain non-demented controls, elderly individuals were recruited in Kitahiroshima, Japan and were evaluated by a questionnaire that included an inquiry into past and present illnesses.…”
Section: Methodsmentioning
confidence: 99%
“…The subjects of this study were 279 control subjects from one of our previous studies [12], 145 patients with probable AD according to the NINCDS/ADRDA criteria [13], and 50 subjects with probable DLB according to the latest consensus diagnostic criteria published in 2005 [11]. To obtain non-demented controls, elderly individuals were recruited in Kitahiroshima, Japan and were evaluated by a questionnaire that included an inquiry into past and present illnesses.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma annexin A5 was quantified using the Chemiluminescent Enzyme Immunoassay (CLEIA) Technique (SphereLight assay) as described (Yamaguchi et al, 2010). Briefly, annexin A5 present in the specimen was trapped by a monoclonal antibody (mAb) against annexin A5 (clone No.…”
Section: Methodsmentioning
confidence: 99%
“…Possibly, Aβ impairs membrane Ca 2+ pumps and enhances Ca 2+ influx through voltage-dependent channels and ionotropic glutamate receptors. Focusing on this mechanism, we identified the Ca 2+ -related protein as a potential biomarker for AD using primary neurons as a cell culture model (Yamaguchi et al, 2010). It was shown that the level of annexin A5 was augmented in both the brain and blood plasma in an AD-model mouse (Tg2576 transgenic mouse), overexpressing mutant human APP (Yamaguchi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations